Effects of microbial inoculant on chemical compositions and in vitro digestibility of elephant grass-based silage - Thanh Loi, Nguyen Thi; Hanh Nguyen, Vu Thi; Quynh Anh, Pham; Ngoc Tung, Quach; Hiep, Tran; Thu An, Nguyen Thi; Hoang Ha, Chu; Quyet Tien, Phi (Vietnam Journal of Biotechnology, 2023)
Probiotic microbial inoculants have been used to improve fermentation quality of green forage feed in pig farming This study aimed to formulate and evaluate effects of microbial inoculants on quality and digestibility of elephant grass-based silage. Green forage formula was made based on economical and agro ingredients resulting in 36% of cost reduction in comparison to the basal diet. The additive containing 1% microbial mixture of Lactobacillus plantarum LCN13, Bacillus velezensis VTX9 and Saccharomyces cerevisiae MCN9 as starter cultures significantly reduced crude fiber (12.39 ± 1.01% Dry Matter (DM)) and neutral detergent fiber concentrations (28.49 ± 0.93% DM) after 120 h (p < 0.05). In contrast, remarkable increases (p < 0.05) were determined in metabolizable energy (2972 ± 18.18% DM) and crude protein (16.32±1.15% DM). These results indicated that metabolic activities by microbial inoculants contributed considerably to the nutritive value of the elephant grass-based diet. The experiment along ensiling time revealed that significant changes in nutritive compositions were observed at 120 h and 168 h (p < 0.05). In support of these results, in vitro digestibility indexes including dry matter, organic matter, and crude protein showed an increasing trend corresponding to ensiling times. Since there were no significant differences between 120 h and 168 h, fermentation time of 120 h was sufficient to obtain desired outcomes. These findings emphasized that elephant grass-based forage fermented with microbial inoculant could be a promising cost-effective and high-quality feed for pig production. Further investigations are required to evaluate safety, growth performance, and pig intestinal microbiota.